Pengaruh Model Cooperative Tipe Think Talk Write terhadap Motivasi Belajar Pendidikan Agama Kristen Siswa dan Budi Pekerti Kelas VIII SMP Negeri 2 Siborongborong Tahun Pembelajaran 2024/2025 - Monalia Simanjuntak; Dorlan Naibaho; Meditatio Situmorang; Pestaria Naibaho; Helena Turnip (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
The purpose of this study was to determine the effect of the Think Talk Write Cooperative Type model on the motivation to learn Christian Religious Education and Character Education of Class VIII Students of SMP Negeri 2 Siborongborong in the 2024/2025 Academic Year. The method used in this study is a quantitative research method. The population is all Christian students of class VIII of SMP Negeri 2 Siborongborong in the 2024/2025 Academic Year totaling 222 people and a sample of 55 people was determined, namely 25% of the population using random sampling techniques. Data were collected with a positive questionnaire of 40 items, namely 25 items for variable X and 15 items for variable Y. The results of the data analysis showed that there was an influence of the Cooperative Think Talk Write Type model on the motivation to learn Christian Religious Education and Character Education of Class VIII Students of SMP Negeri 2 Siborongborong in the 2024/2025 Academic Year as evidenced by the following data analysis: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.584> rtable ( = 0.05, n = 55) = 0.226. b) Significant relationship test obtained tcount = 5.232> ttable ( = 0.05, dk = n-2 = 53) = 2,000. 2) Influence test: a) Regression equation test, obtained regression equation . b) Regression determination coefficient test (r2) = 34.1%. 3) Hypothesis testing using the F test obtained Fcount > Ftable = ( = 0.05, df numerator k = 25, df denominator = n-2 = 55-2 = 53) which is 27.26 > 1.39. Thus Ha is accepted and H0 is rejected.